Erratum: Using the Mixed-Meta Method to Assess Portfolios in Science Teaching - Yaşar, Mehmet Diyaddin; Batdi, Veli; Kilinç, Büşra; Kiliç, Ayşe Nur (Science Insights Education Frontiers, 2024)
The corrections should be made as below, The (Alkan et al., 2019) used in the Methods section needs to be deleted. The Alkan et al. study is a mixed method [(Mixed methods design: a narrative literature review. Journal of Qualitative Research in Education, 7(2):559-582)]. However, the term used in our study is mixed-meta method. In addition, the term belongs to a different author and it has a completely different definition. (On the pages 3900 and 3914). Instead of “(Büyüköztürk et al., 2018 p.259-260)” (Batdı, 2020, p.3) should be added under the title “Meta-analysis procedure”. (On the page 3903).